A temática juventude em periódicos brasileiros da área de economia : uma revisão sistemática de literatura - Souza, Joici Cristiani de (2022)
This work aims to identify which were the most studied subjects in this decade about young people and how often they are addressed in Brazilian economic research from 2010 to 2020. A Systematic Literature Review was carried out, based on a keyword search, all articles from 11 Brazilian economic journals were searched. From this research, it was observed that subjects such as the Labor Market and Education were the themes most developed by the works studied. The period with the highest number of publications related to the topic was 2020